3D Nanolithography by Means of Lipid Ink Spreading Inhibition (Small 10/2023). Issue 10 (10th March 2023) - Berganza, Eider; Boltynjuk, Evgeniy; Mathew, George; Vallejo, Fabio Fernando; Gröger, Roland; Scherer, Torsten; Sekula‐Neuner, Sylwia; Hirtz, Michael
Abstract : Lipid Ink Spreading Inhibition In article number 2205590, Eider Berganza, Michael Hirtz, and co‐workers utilize dip‐pen nanolithography to print lipid patches layer‐by‐layer forming 3D structures on a surface coated with serum albumin stabilizing the structures. The lipid molecules transfer from the probe to the substrate through a water meniscus. To further improve their stability, lipid‐structures get covered with a few nanometers of gold through physical vapor deposition.